A concepção de avaliação educacional veiculada na produção acadêmica do Programa de Pós-Graduação em Educação: Currículo (1975-2000) - Teixeira, Célia Regina (2006)
The objective of this study is to document, organize and understand the conception of EDUCATIONAL ASSESSMENT diffused in the academic production of the Education Post-Graduate Program: São Paulo Pontifícia Universidade Católica Syllabus between 1975 and 2000. Of the State of the Art and State of Knowledge study in the academic production, composed of doctoral theses and master s dissertations on educational assessment (1975-2000), 22 works were selected covering the conceptions of educational assessment produced in the Education Post-Graduate Program: Syllabus in the above mentioned period. The research was contextualized by outlining the setting composed of the post-graduate program and the conceptions of thesis and dissertation professor-tutors, based on a qualitative approach. Thesis and dissertation abstracts were analyzed and organized by using the following descriptors: theme, scope, highlighted aspects and contributions to the educational assessment conception. The research indicates that the Education Post-Graduate Program: Syllabus presents a significant set of production in the area of educational assessment, and it has become a national reference. It was possible to observe a movement in the educational assessment conceptions, which, having started with a measuring view, move towards an emancipatory view, which represents a pioneering mark in Brazilian assessment studies